miRNA-431 Prevents Amyloid-β-Induced Synapse Loss in Neuronal Cell Culture Model of Alzheimer's Disease by Silencing Kremen1 - Ross, Sean P.; Baker, Kelly E.; Fisher, Amanda; Hoff, Lee; Pak, Elena S.; Murashov, Alexander K. (Frontiers in Cellular Neuroscience, 2018)
Synapse loss is well regarded as the underlying cause for the progressive decline of memory function over the course of Alzheimer’s disease (AD) development. Recent observations suggest that the accumulation of the Wnt antagonist Dickkopf-1 (Dkk1) in the AD brain plays a critical role in triggering synaptic degeneration. Mechanistically, Dkk1 cooperates with Kremen1 (Krm1), its transmembrane receptor, to block the Wnt/β-catenin signaling pathway. Here, we show that silencing Krm1 with miR-431 prevents amyloid-β-mediated synapse loss in cortico-hippocampal cultures isolated from triple transgenic 3xTg-AD mice. Exposure to AβDDL (an amyloid-β derived diffusive ligand) or Dkk1 reduced the number of pre- and postsynaptic puncta in primary neuronal cultures, while treatment with miR-431 prevented synapse loss. In addition, treatment with miR-431 also prevented neurite degeneration. Our findings demonstrate that miR-431 protects synapses and neurites from Aβ-toxicity in an AD cell culture model and may be a promising therapeutic target.